2006 International Conference of the IEEE Engineering in Medicine and Biology Society 2006
DOI: 10.1109/iembs.2006.259360
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Imaging Aid for the Blind

Abstract: To explore the efficacy of using a far infrared thermal camera with a haptic display to assist blind people in identifying humans, we performed experiments with a prototype device on five low-vision (functionally blind) subjects. Infrared allows for easy detection of human shape due to typically high contrast in temperatures from a person against their surrounding environment. Infrared cameras can be made small and inexpensive with uncooled microbolometer technology. Our study showed a great willingness by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Researchers have developed prototypes where thermal imaging is paired with a haptic display as an aid for the blind [24] or used with the Argus II system in lieu of the visible-light camera [23,[25][26][27][28]. Subjectively, the users were 'uniformly fascinated by the device' [24] and 'thought it would indeed be very useful and would increase the daily use of the Argus II' [25].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have developed prototypes where thermal imaging is paired with a haptic display as an aid for the blind [24] or used with the Argus II system in lieu of the visible-light camera [23,[25][26][27][28]. Subjectively, the users were 'uniformly fascinated by the device' [24] and 'thought it would indeed be very useful and would increase the daily use of the Argus II' [25].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have developed prototypes where thermal imaging is paired with a haptic display as an aid for the blind [24] or used with the Argus II system in lieu of the visible-light camera [23,[25][26][27][28]. Subjectively, the users were 'uniformly fascinated by the device' [24] and 'thought it would indeed be very useful and would increase the daily use of the Argus II' [25]. Objectively, the users were able to use thermal imaging to complete tasks that involve detecting and locating heat-emitting targets [23][24][25][26][27][28], and the responses were faster and more accurate when compared to using a visible-light camera [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the markets driving commercial thermal imagining is the automotive market, where thermal imagining is used for pedestrian and car detection for increased security and collision avoidance [ 12 , 13 , 14 ]. However, there are other applications such as object inspection in construction [ 15 , 16 , 17 ], medicine [ 18 , 19 ], veterinary science [ 20 ], access control [ 21 ], agriculture [ 22 ], astronomy [ 23 , 24 ], gas leakage detection [ 25 , 26 ], inspection of solar panels [ 27 ], autonomous drone navigation [ 28 ], helping visually impaired subjects [ 29 ], and so on. While a more in-depth presentation of thermal imaging applications can be found in [ 2 , 30 ]; the application range is evident and diverse.…”
Section: Related Work and Contributionsmentioning
confidence: 99%
“…This reduced set of information is potentially useful to a visually-impaired person for interaction and navigation while allowing easier interpretation relative to other imaging technology. Pilot studies by Hedin et al [3] suggested the feasibility and utility of scanning space in with a far-infrared sensitive thermal camera and converting portions to a thin tactile array. In this set of experiments, we tested the efficacy of a handheld scanning device that mapped far-infrared images onto a vertically oriented 4x24 tactile pin array for the purpose of locating people in space.…”
Section: Introductionmentioning
confidence: 98%